Effect of Employees’ Commitment on Organizational Performance in Selected Firms - Ogala S. C (RIRAI Publisher, 2020)
This study investigated the effect of employee’s commitment on organizational performance in selected brewing firms. Two objectives which are ;To examine the impact of employee commitment on organizational profitability in brewing industry in Nigeria To examine the dimensions of employee commitment on performance in brewing industry in Nigeria guided the study. Also two research questions and hypotheses were drawn along that line. A survey design was adopted with a sample population size of 216 drawn using Taro Yamani. Data were presented and analyzed using tables and simple percentages. Also, hypotheses were tested using parametric statistics. Findings revealed that Organizational profitability had a positive influence on employees performance in the area studied (Zc=4.226 > Zt =1.645) and Inadequate employees development programmes had a positive influence on employees commitment in the area studied (Zc=4.531 > Zt =1.645). It was recommended that Organizations should regularly embark on performance appraisals because; it will go a long way to know whether the human capital development is producing the needed result and that there should be a systematic view towards employees’ commitment development in organizations. That is to say all levels, sections should be given equal opportunity to develop. As generally stated, if you fail to plan, then you are planning to fail